Lattice-matched carbon dots induced the oriented self-assembly of Cu nanoparticles. (July 2017) - Cao, Piao-Yang; Liu, Yong-Lin; Lin, Zuan-Tao; Huang, Jian-Fei; Chen, Wen-Zhao; Liang, Jun-Hua; Zhou, Wuyi; Jiang, Gang-Biao
Abstract: Orientation-induced crystallization is a widely applied method of forming crystal with highly oriented structure. Here, we reported a promising matrix for orientation-induced crystallization–carbon dots (CDs), who exhibited high lattice-matching with Cu crystal. First, CDs induce self-assembly of Cu nanoparticles through organics-inorganics interface interaction, forming self-assembled mesocrystal and single crystal with large size. Second, the CDs selectively deposit on Cu {111} plane via lattice-matching, endowing Cu self-assemblies with tunable morphology including sphere, truncated octahedron, octahedron, concave octahedron and hexpods. Third, CDs also protect Cu self-assemblies from oxidation and act as efficient interface for optical conversion and electron transfer. So using as surface-enhanced Raman scattering (SERS) substrate for the first time, the CDs-coating hexpods Cu mesocrystal require no post processing and exhibit high stability and surface-enhanced Raman scattering (SERS) activity which ordinary Cu nanostructure cannot achieve. Graphical abstract: CDs induce self-assembly of Cu nanoparticles through organics-inorganics interface interaction, forming self-assembled mesocrystal and single crystal with large size. CDs selectively deposit on Cu {111} plane via lattice-matching and epitaxial growth, endowing Cu self-assemblies with tunable morphology including sphere, truncated octahedron, octahedron, concave octahedron and hexpods.